1986
DOI: 10.1177/027836498600500217
|View full text |Cite
|
Sign up to set email alerts
|

Type Selection of Robot and Gripper Kinematic Topology Using Expert Systems

Abstract: Robots are used for many different applications including underwater recovery, welding, inspection, pick-and-place operations, space exploration, and assembly. Each task im parts different functional demands on the robot topology including the gripper. An improper choice of the basic kine matic chain may demand sophisticated control algorithms to undo poor type selection. This paper suggests techniques of type synthesis based on graph theory and expert systems that will aid in proper kine matic topology. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 4 publications
0
12
0
Order By: Relevance
“…In some applications (Erdman 1986;Soni 1988;Hoeltzel 1990), expert systems have been adopted to establish a structure-to-function mapping with a certain success, while more is expected from further developments in artificial intelligence techniques. As far as bevel gear wrist mechanisms are concerned, the algorithm proposed herein for drawing functional representations corresponding to a given graph can be regarded as the first preliminary phase of a more general inverse procedure for selecting the topology that best suits a given industrial application.…”
Section: Developing Of An Atlas Of Functional Representationsmentioning
confidence: 99%
“…In some applications (Erdman 1986;Soni 1988;Hoeltzel 1990), expert systems have been adopted to establish a structure-to-function mapping with a certain success, while more is expected from further developments in artificial intelligence techniques. As far as bevel gear wrist mechanisms are concerned, the algorithm proposed herein for drawing functional representations corresponding to a given graph can be regarded as the first preliminary phase of a more general inverse procedure for selecting the topology that best suits a given industrial application.…”
Section: Developing Of An Atlas Of Functional Representationsmentioning
confidence: 99%
“…As conceptual design of mechanical transmission system has an essential effect on product innovation, many researches have been focused on it in recent decades with many valuable fruits [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The former approaches [4][5][6] are based on that existing mechanisms are composed of a set of functional elements, with which new mechanisms that can deliver desired functions can be synthesized. The latter approaches [7][8][9] However, the current approaches always focus on the automated synthesis method of SISO systems, and would fail to yield feasible solutions to MIMO system.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, application of artificial intelligence concepts and techniques in engineering design has been recognized and explored. Several research projects (Erdman et al, 1986;Kota et al, 1987a, b;Hoeltzel et al, 1987;Tang and Roll, 1988;Yang et al, 1988a-c;Rehg et al, 1988) have shown tremendous advantages of artificial intelligence techniques over traditional manual and conventional computer approaches. Among the applications in the field of engineering design, the technology of knowledge-based systems is most promising and successful so far.…”
Section: Introductionmentioning
confidence: 99%